2005
DOI: 10.1158/1078-0432.ccr-04-2086
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cystatin C is a Better Marker of Topotecan Clearance than Serum Creatinine

Abstract: Purpose: To evaluate plasma cystatin level as a covariate to predict topotecan pharmacokinetics.Cystatin C, a member of the cystatin superfamily of cysteine proteinase inhibitors, has been recently proposed as an alternative endogenous marker of glomerular filtration. Renal function is known as a key factor of topotecan clearance. Experimental Design: Data were obtained from 59 patients who underwent drug monitoring for individual dosing of topotecan. Topotecan plasma concentrations versus time were analyzed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Second, it has been shown that CysC is a good renal biomarker in children with sepsis (28) and that CysC-based GFR estimations remain accurate in children presenting with hyperfiltration (in contrast to Scr-based formulae) (24). Finally, CysC was found to better predict elimination of renally excreted drugs in adults compared to Scr or CrCL (29)(30)(31)(32). This is only the second report to identify this new biomarker as a predictor of renal drug clearance in children at the expense of Scr or CrCL (33).…”
Section: Discussionmentioning
confidence: 99%
“…Second, it has been shown that CysC is a good renal biomarker in children with sepsis (28) and that CysC-based GFR estimations remain accurate in children presenting with hyperfiltration (in contrast to Scr-based formulae) (24). Finally, CysC was found to better predict elimination of renally excreted drugs in adults compared to Scr or CrCL (29)(30)(31)(32). This is only the second report to identify this new biomarker as a predictor of renal drug clearance in children at the expense of Scr or CrCL (33).…”
Section: Discussionmentioning
confidence: 99%
“…It concluded that this new parameter was not superior to creatinine in predicting drug clearance. However, these results were rapidly refuted (261) and two studies based on population pharmacokinetics methodology, the most robust in this field, definitively demonstrated the utility of CysC in predicting the clearance of drugs which were eliminated either exclusively or only partially by the kidneys, i.e., two cytotoxic agents, topotecan (262) and carboplatin (263). Interestingly, both of these studies showed an advantage of combining CysC with creatinine rather than using either individually.…”
Section: Cysc and Drug Monitoringmentioning
confidence: 99%
“…We recommend the use of the particle-enhanced nephelometric immunoassay or particle-enhanced turbidimetric immunoassay method to determine cysC for individual carboplatin dosing. Lastly, because carboplatin elimination is highly dependent on renal function, the benefit of considering cysC for individual dosing should also exist for other renally cleared drugs such as topotecan in Oncology (23), and aminoglycosides in Infectious Diseases (24).…”
mentioning
confidence: 99%